Structural damage identification of steel-concrete composite bridge under temperature effects based on cuckoo search. (25th June 2019) - Huang, Minshui; Cheng, Shaoxi; Lu, Hailin; Gul, Mustafa; Zhang, Haiyang
Civil structures are generally exposed to varying temperature conditions. Temperature variations in structural components not only cause quasi-static responses like displacement and stress, but also lead to changes in vibration features, such as frequencies and mode shapes. Damage identification is usually based on the vibration characteristics, which is easily affected by temperature. This means that the accuracy of identification is not guaranteed without considering the temperature effects. In the paper, temperature is considered as a variable in material properties, and the finite element model of I-40 steel-concrete composite bridge is established based on MATLAB platforms in order to figure out its vibration features. Then cuckoo search (CS) is introduced to damage identification under temperature variations. It is shown that cuckoo search is able to distinguish experimental structure damages from temperature variations.